KAJIAN STRUKTUR ANATOMI DAN MORFOLOGI DAUN PLANLET PISANG KEPOK KUNING HASIL PEMBERIAN EKSTRAK UMBI KEMBANG SUNGSANG SECARA IN VITRO - Yoga Aji Saputra; Eti Ernawiati; Rochmah Agustrina; Sri Wahyuningsih (Jurnal Biosilampari : Jurnal Biologi, 2021)
Plantain is a fruit commodity that has a high level of market demand, but the yield is low. To overcome this problem, tissue culture techniques are used to increase plantlet production in a short time. Plantain have parthenocarpy character, high sterility, and different levels of ploidy. Tissue culture with the addition of flame lily tuber biomutagen containing colchicine was used as a strategy to overcome the above constraints because it was thought to increase the production of polyploid banana plantlets. Changes in the anatomical and morphological structures are indicators of polyploidy. The purpose of this study was to obtain information on changes in the anatomical and morphological structures of plantain leaves as a result of giving in vitro plantlet propagation media as an indicator of the formation of polyploidy. Plantlets were grown on tissue culture media supplemented with three treatments: 10% flame lily tuber extract, 0.1% pure colchicine, and without addition (control). The parameters observed were epidermal cell size, stomata size, stomata index, number and leaf area. Epidermal cell size, stomata size and stomatal index were analyzed using range values ​​and mean values. The number of leaves, and the average wide of leaf, is then shown in the form of a bar chart. The results showed that administration of flame lily tuber extract was able to increase epidermal cell size, stomata size, wide of a leaf, and able to reduce the stomata index and number of leaves.